The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1063/1.3245162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ion temperature on oblique propagation of large amplitude solitary kinetic Alfvén waves

Abstract: The effect of ion temperature on the existence of large amplitude solitary kinetic Alfvén waves and double layers are investigated in a two-fluid model using Sagdeev’s pseudopotential technique. The ion temperature, obliqueness parameter, and the ratio of cyclotron frequency to ion frequency are found to play significant roles in the formation and the shape of solitary kinetic Alfvén waves and double layers. Hump-type solitary waves and dip-type double layers are also observed. Conditions for the existence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
1
1
Order By: Relevance
“…The effect of ion thermal temperature on soliton width is shown in figure 5 from which it can be inferred that ion thermal temperature has no significant influence on the width of solitary KAWs. That the ion thermal temperature producing no significant effect on solitary KAWs contrasts with earlier reports [45,47,48] where ion temperature seems to play an important role on soliton characteristics in nondegenerate plasmas. In connection with the results presented above, it needs to be mentioned here that as we are dealing with zero thermal temperature degenerate electrons and positrons, the correction due to q-nonextensivity of electrons and positrons vanishes [49].…”
Section: Resultscontrasting
confidence: 99%
“…The effect of ion thermal temperature on soliton width is shown in figure 5 from which it can be inferred that ion thermal temperature has no significant influence on the width of solitary KAWs. That the ion thermal temperature producing no significant effect on solitary KAWs contrasts with earlier reports [45,47,48] where ion temperature seems to play an important role on soliton characteristics in nondegenerate plasmas. In connection with the results presented above, it needs to be mentioned here that as we are dealing with zero thermal temperature degenerate electrons and positrons, the correction due to q-nonextensivity of electrons and positrons vanishes [49].…”
Section: Resultscontrasting
confidence: 99%
“…Prasanta Chatterjee etal. [29], have recently studied the effect of ion-temperature on large-amplitude kinetic solitary waves and concluded that the ion temperature has important effect on shape of solitary kinetic Alfvén waves and doublelayers. Current investigation is an attempt to study the most general cases of electron-ion and electron-positron-ion three dimensional plasmas consisting of warm electrons/positron and ions considering the two dimensional drifts of ions.…”
mentioning
confidence: 99%